LAMPU SEBAGAI SIMBOL DALAM SENI LUKIS SUREALIS - M. Yasir, Drs. Abd. Hafiz, M.Pd, Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2017)
The purpose of this final paper is to visualize the lights as a symbol the phenomenon of problems that occur in Indonesia.Lights become symbols of messages to deliver news or information about problems that have occurred lately. To creating of art there are several methods in realizing art ideas preparation is the search for ideas, elaboration, synthesis, concept realization, exhibition. As for the 10 titles of works that have been created are: 1. Build but tear down. 2. Fertile but arid. 3. Life is not life. 4. Golf and Gold 5. up. 6. The Law of death. 7. An educational dilemma 8. Fake podium 9. One voice 10. Naturalistrik.Kata Kunci: Lampu, Fenomena kekinian, Lukis, Surealisme